2003
DOI: 10.1093/aje/kwg067
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in a Population-based Cohort of Men and Women in Registered Homosexual Partnerships

Abstract: Cancer patterns among broad populations of homosexual men and women have not been studied systematically. The authors followed 1,614 women and 3,391 men in Denmark for cancer from their first registration for marriage-like homosexual partnership between 1989 and 1997. Ratios of observed to expected cancers measured relative risk. Women in homosexual partnerships had cancer risks similar to those of Danish women in general (overall relative risk (RR) = 0.9, 95% confidence interval (CI): 0.6, 1.4), but only one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 24 publications
1
68
1
Order By: Relevance
“…Men who had practiced anal sex with two or more female partners were also at increased risk, but numbers were unstable. Although some study participants may have been reluctant to report certain sexual details, the finding that men with same-sex experience are not at increased risk of developing penile SCC accords well with prior reports of no conspicuous penile SCC risk in gay men (4,24).…”
Section: Discussionsupporting
confidence: 83%
“…Men who had practiced anal sex with two or more female partners were also at increased risk, but numbers were unstable. Although some study participants may have been reluctant to report certain sexual details, the finding that men with same-sex experience are not at increased risk of developing penile SCC accords well with prior reports of no conspicuous penile SCC risk in gay men (4,24).…”
Section: Discussionsupporting
confidence: 83%
“…In one study there were significantly higher rates of cervical cancer in both lesbian and bisexual women, and higher rates of uterine cancer in lesbians but lower rates in bisexual women 35. Another study found lower rates of cervical carcinoma in situ in lesbians 36. There was no significant difference in rates of endometriosis and fibroids 12, 31, 37.…”
Section: Resultsmentioning
confidence: 96%
“…Among 5000 Danish persons in same-sex partnerships, there was no evidence of an increased cancer incidence, except among gay men with AIDS. 4 …”
Section: Cancer Survivorship and Sexual Orientationmentioning
confidence: 99%